Structures, Substrates, and Regulators of Mammalian Sirtuins – Opportunities and Challenges for Drug Development - Moniot, Sebastien; Weyand, Michael; Steegborn, Clemens (Frontiers in Pharmacology, 2012)
Sirtuins are NAD+-dependent protein deacetylases regulating metabolism, stress responses, and aging processes. Mammalia have seven Sirtuin isoforms, Sirt1-7, which differ in their substrate specificities and subcellular localizations. The physiological functions of Sirtuins make them interesting therapeutic targets, which has stimulated extensive efforts on development of small-molecule Sirtuin modulators. Yet, most Sirtuin inhibitors show limited potency and/or isoform specificity, and the mechanism of Sirtuin activation by small molecules remains obscure. Accumulating information on Sirtuin substrates, structures, and regulation mechanisms offer new opportunities for the challenging task to develop potent and specific small molecule modulators for mammalian Sirtuins for in vivo studies and therapeutic applications. We therefore recapitulate advances in structural and mechanistic studies on substrate recognition and deacetylation by Sirtuins, and in the characterization of compounds and molecular mechanisms regulating their activity. We then discuss challenges and opportunities from these findings for Sirtuin-targeted drug development efforts.